Perfil pró-oxidante periférico e sistêmico em ratos Wistar induzidos ao pré-diabetes - Zacarias, Gustavo Castillo [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Dexamethasone-induced insulin resistance contributes to cardiometabolic dysfunction and predisposes to oxidative stress (OS). However, evidence on the role of aerobic physical training (APT) in mitigating systemic and peripheral oxidative stress in this model is limited. This study aimed to assess the effect of aerobic physical training on systemic and peripheral OS in a dexamethasone-induced insulin resistance model. Eight-week-old male Wistar rats (250g) were divided into four groups: CS (sedentary control), CT (trained control), DS (dexamethasone sedentary), and DT (dexamethasone trained), with 7-9 rats per group. Insulin resistance was induced by intraperitoneal injection of dexamethasone (1 mg/kg of body weight) during the last 5 days of training. Aerobic physical training was conducted on a treadmill after a maximal exertion test (60% intensity, 1 hour/day, 5 days/week for 8 weeks). Plasmatic triglycerides (TG) and glucose levels were measured using a biochemical analyzer (A15, BioSystems). Plasma and anterior tibial muscle samples were collected for OS analysis, assessing pro-oxidant markers (hydrogen peroxide [H2O2] concentration and NADPH oxidase activity) and nitric oxide bioavailability (nitrite concentration). Statistical analysis was performed using one-way ANOVA with Tukey’s post-hoc test (p<0.05). The results showed no significant differences in glucose levels among groups. Plasma TG levels were elevated in dexamethasone-treated groups compared to controls (CS: 102.33±36.34; CT: 112.66±38.19; DS: 206.22±63.81; DT: 205.55±86.81 [mg/dL], p<0.01). H2O2 levels in tibial muscle were increased in the DS group compared to DT (CS: 8.25±1.21; CT: 8.48±1.72; DS: 9.64±1.92; DT: 7.30±1.31 [µM/H2O2], p=0.04). No significant differences were found in NADPH oxidase activity or nitrite levels in tibial muscle. In plasma, H2O2 levels were elevated in the DT group compared to CT (CS: 24.25±7.37; CT: 17.10±7.35; DS: 24.21±11.04; DT: 32.12±7.84 [µM/H2O2], p=0.01). Similar to the tibial muscle, no significant differences were found in plasma NADPH oxidase activity or nitrite levels among groups. A positive correlation was observed between NADPH oxidase activity and H2O2 concentration in plasma (r=0.51, p<0.01). In conclusion, peripheral and systemic hydrogen peroxide levels increased in groups with dexamethasone-induced pre-diabetes. However, aerobic physical training mitigated H2O2 levels in muscle tissue, indicating a potential protective effect of aerobic physical training against oxidative stress in muscular tissues.

A resistência à insulina ocasionada pela dexametasona contribui com prejuízos cardiometabólicos e predispõe o estresse oxidativo (EO). Contudo a contribuição do treinamento físico (TF) aeróbio em mitigar alterações de estresse oxidativo sistêmico e periférico neste modelo é escassa. O objetivo deste trabalho é avaliar o efeito do TF aeróbio sobre EO sistêmico e periférico em modelo de resistência à insulina por dexametasona. Os métodos contemplam: Ratos Wistar (8 semanas, 250g) foram separados em 4 grupos (CS [controle sedentário], CT [controle treinado], DS [dexametasona sedentário] e DT [dexametasona treinado], n=7-9/grupo). A dexametasona foi administrada por injeção intraperitoneal (1mg/kg de peso) nos últimos 5 dias de treinamento para indução da resistência à insulina. O TF aeróbio foi realizado em esteira adaptada após teste de esforço máximo [intensidade de 60%, 1 hora por dia, 5 dias/ semana durante 8 semanas]. Triglicérides plasmáticos (TG) e glicemia foram medidos por analisador bioquímico-A15 (BioSystems). O plasma e o músculo tibial anterior foram utilizados para análises de EO sendo avaliados marcadores pró oxidantes (concentração de peróxido de hidrogênio [H2O2] e atividade da NADPH oxidase) e biodisponibilidade de óxido nítrico (concentração de nitrito). Foi utilizada ANOVA one-way com post-hoc de Tukey (p<0.05) para a análise dos dados. Em relação aos resultados, não houve diferença significativa na glicemia entre os grupos. Houve aumento de TG plasmáticos em ambos os grupos (dexametasona comparados aos grupos controle) (CS: 102.33±36.34, CT: 112.66±38.19, DS: 206.22±63.81, DT: 205.55±86.81 [mg/dL], p<0.01). No músculo tibial houve aumento da concentração de H2O2 no grupo DS comparado a DT (CS: 8.25±1.21, CT: 8.48±1.72, DS: 9.64±1.92, DT: 7.30±1.31 [µM/H2O2], p=0.04). Não houve diferença significativa na atividade da NADPH oxidase e nitritos no músculo tibial. Com relação ao plasma, observou-se aumento da concentração de H2O2 no grupo DT comparado ao CT (CS: 24.25±7.37, CT: 17.10±7.35, DS: 24.21±11.04, DT: 32.12±7.84, [µM/H2O2], p=0.01). Semelhante ao tibial, não houve diferença significativa na atividade da NADPH Oxidase e concentração de nitrito plasmático entre os grupos. No entanto, houve correlação positiva entre a atividade da NADPH Oxidase e a concentração de H2O2 no plasma (r=0.51, p<0.01). Conclui-se então que há um aumento de peróxido de hidrogênio periférico e sistémico nos grupos induzidos ao pré-diabetes, no entanto, a nível muscular, há uma atenuação ocasionada pelo treinamento físico aeróbio.
Perfil prooxidante periférico y sistémico en ratas Wistar inducidas con prediabetes
Keywords: Pré-diabetes; Ratos Wistar; Leitura (Ensino superior); Reading (Higher education)